A submaximal treadmill test to predict critical speed - Follador, L.; de Borba, E. F.; Neto, A. L. B.; da Silva, S. G. (Journal of Sports Sciences, 2021)
We assessed the reliability and validity of a 10-min submaximal treadmill test (T10) to predict critical speed (CS). Forty-two runners completed a familiarization trial plus two experimental trials (T10 test and T10 retest). Reliability between the T10 test and T10 retest was assessed using coefficient of variation (CoV), limits of agreement (LoA) and intraclass correlation (ICC). For validity, the speed from the T10 retest was compared with the CS determined from 3 runs on separate days on a running track over 1200, 2400, and 3600 m (field test). Reliability between the T10 test and T10 retest showed a CoV of 3.4%, LoA of 0.05 ± 0.39 m.s-1, and an ICC of 0.93. Validity showed that speed (m.s-1) (T10 retest: 3.86 ± 0.51; field test: 3.88 ± 0.55) did not differ between trials. The T10 retest was highly correlated with the field test, r = 0.93, and the standard error for the estimate of CS using the T10 retest was 0.06 m.s-1, and the LoA was 0.02 ± 0.40 m.s-1. A submaximal 10-min treadmill test (T10) provides a practical and accessible method to estimate CS.